Flow control of non-slender delta wings by leading-edge modifications. (12th March 2020) - Rein, Martin; Busse, Felix; Edzards, Frank; Haselmeyer, Hartmut; Höhler, Gebhard; Siegel, Lars
Abstract: Different concepts for controlling a non-slender delta wing are considered and compared with each other. The concepts are based on geometrical modifications of the leading edges. The strategy aims at producing an asymmetric distribution of lift due to vortices on the left and right wing half and thus, for example, rolling moments to be used in controlling the model. The effectiveness of different approaches is determined in low-speed wind tunnel tests both by measuring forces and moments acting on the model and by investigating the flow field around the model by particle image velocimetry and oil-flow visualization of skin friction lines. Two approaches are pursued. One is based on static and dynamic actuators acting at the left leading-edge. The other uses different combinations of leading edge shapes on the two halves of the model. Finally, the effect of asymmetric boundary layer tripping is briefly considered.